Application of the hydrogen microprint and the microautoradiography techniques to a duplex stainless steel - (:unkn) unknown (My University, 1995)
Hydrogen microprint (HMT) and microautoradiography (HMAT) techniques have been used to study the hydrogen distribution in the microstructure of a duplex stainless steel having a 50 50 austenite/ferrite phase ratio. Both techniques indicated that the austenite/ferrite interphase boundaries and the austenite phase could act as effective hydrogen traps in steel microstructure. The HMT and HMAT results confirm the ideas that the grain boundary diffusivity of hydrogen is concentration-dependent and that the grain boundaries are not high-diffusivity paths for hydrogen. © 1995.